Bathyraja meridionalis, Darkbelly Skate - Pollom, R. (2020)
The Darkbelly Skate (Bathyraja meridionalis) is a large (to 158 cm total length) that occurs in the Southeast Pacific Ocean off Magallanes Province, Chile, in the Southwest Atlantic Ocean from Buenos Aires to Tierra del Fuego, Argentina and westward to the Falkland Islands (Malvinas), and in the Antarctic Atlantic Ocean around the Shag Rocks and South Georgia. It is demersal on continental and insular shelves and slopes at depths of 65?2,240 m, and is captured in demersal trawl and longline fisheries targeting skates, Patagonian Toothfish, and other finfishes. It has substantial refuge at depth and its population is suspected to be stable. Therefore, the Darkbelly Skate is assessed as Least Concern.